AN ANALYSIS ON THE CONTENT VALIDITY OF REGIONAL ENGLISH TEST ITEMS OF SMP NEGERI 2 KEBAKKRAMAT KARANGANYAR - PRASETYO, JOKO (2010)
In teaching learning process, teachers convey the materials from early until the end of teaching learning period. In the end of teaching learning period, teachers need a test. Test is an activity used to measure the ability of the students in teaching learning process. The test which is given to the students must have the qualities or characteristics; they are practicality, reliability, and validity. The most important validity from the test is content validity. The objectives of this study are 1) To describe the content validity of reading test items based on syllabus of School Based-Curriculum that the students are expected to understand the short functional text and short simple essay, 2) To describe the content validity of writing test items based on syllabus of School Based-Curriculum that the students are expected to express the short functional text and short simple essay. The primary data are Regional English test items for the first and second semester test of SMP in Karanganyar region. The data were collected by finding and learning the test items, reading the test items to get more understanding, observing the test items, selecting and categorizing data, arranging and developing the selecting data. Then the data were analyzed by using indicators of School Based-Curriculum. The result of this study shows that 1) the content of Regional English test items for reading skill is valid based on School Based-Curriculum. It is based on the following evidences: a) Reading skill is very good (100%) for the first semester, b) the second semester reading skill is very good (84.62%). 2) the content of Regional English test items for writing skill is not valid based on School Based-Curriculum. It is based on the following evidences: a) Writing skill is fair (42.86%) for first semester, b) the second semester writing skill is fair (52.63%).